2017
DOI: 10.1136/annrheumdis-2016-210711
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of glucocorticoids, conventional and targeted synthetic disease-modifying antirheumatic drugs: a systematic literature review informing the 2016 update of the EULAR recommendations for the management of rheumatoid arthritis

Abstract: ObjectivesTo perform a systematic literature review (SLR) informing the 2016 update of the recommendations for the management of rheumatoid arthritis (RA).MethodsAn SLR for the period between 2013 and 2016 was undertaken to assess the efficacy of glucocorticoids (GCs), conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and targeted synthetic DMARDs (tsDMARDs) (tofacitinib and baricitinib) in randomised clinical trials.ResultsFor GCs, four studies were included in the SLR. Patients without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 31 publications
2
88
0
5
Order By: Relevance
“…In addition, observational studies addressing tsDMARDs (Jak inhibitor(s)) have not yet been found. However, RCT data point towards a higher risk of serious infections, infections caused by herpes zoster and tuberculosis, risks that should not be ignored and that warrant further research 2 60. Finally, while glucocorticoids are gaining importance as bridging treatment for RA, no single study meeting the eligibility criteria could be found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, observational studies addressing tsDMARDs (Jak inhibitor(s)) have not yet been found. However, RCT data point towards a higher risk of serious infections, infections caused by herpes zoster and tuberculosis, risks that should not be ignored and that warrant further research 2 60. Finally, while glucocorticoids are gaining importance as bridging treatment for RA, no single study meeting the eligibility criteria could be found.…”
Section: Discussionmentioning
confidence: 99%
“…This SLR is an update of the SLR performed previously for the corresponding 2013 update of the RA management recommendations 6. The results of this and two other SLRs2 3 provided the task force with the current state of evidence.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Согласно данным Британско-го регистра генно-инженерных биологических препара-тов (ГИБП) в ревматологии, в среднем 50% пациентов прекращают лечение первым ГИБП в течение 5 лет пос-ле его назначения из-за недостаточной эффективности или неблагоприятных реакций [1]. Ремиссии через 6 мес от начала терапии стандартными базисными противо-воспалительными препаратами (БПВП), по данным рандомизированных контролируемых исследований (РКИ), достигают лишь 1,6-2,6% больных РА и 7,2-16% пациентов в группах, получающих помимо БПВП то-фацитиниб [2]. По данным РКИ С-EARLY [3], после 10-13 мес приема метотрексата (МТ) ремиссия по кри-териям Европейской антиревматической лиги (EULAR) была достигнута у 15%, а в группе получающих наряду с МТ цертолизумаба пэгол -у 29% больных РА.…”
unclassified
“…Nevertheless, after a long debate regarding csDMARD combinations, the task force arrived at the decision to recommend primarily the use of methotrexate (MTX) monotherapy plus short-term glucocorticoids (GC). The decision to delete combinations of csDMARDs as a major recommendation was based on the evidence provided by the respective systematic literature reviews (SLR) 3. Indeed, several new data revealed that MTX+GC was as efficacious as csDMARD combinations+GC, but significantly safer 4–6.…”
mentioning
confidence: 99%